Physical characterization of a trypanosoma (Nannomonas) congolense metacyclic- specific variable surface glycoprotein expression site. - Doshi, N.R. (University of Nairobi, 1993)
Trypanosomes are unicellular protozoans that alter their hosts I immune response by antigen variation; a process during which the trypanosome periodically switches the antigen profile of the variable surface glycoprotein (VSG), an immunodominant molecule that covers its entire surface. The VSGs are expressed by only two life cycle stages of the trypanosome: the bloodstream forms which express the blood stream form VSGs (bVSGs) and the metacyclic forms which express the metacyclic form mVSGs (mVSGs). In this investigation, a region in the immediate upstream vicinity of an mVSG gene of T. congolense IL3000 has been analysed. Restriction enzyme digestion and Southern blot hybridization analyses revealed that the expression site of this gene does not contain significant stretches of DNA sequences devoid of restriction enzyme sites, nor does it contain highly repetitive DNA sequences analogous to those observed in the vicinities of some of the VSG genes of T. brucei. Northern blot hybridizations, indicated the presence of at least two distinct transcripts, each from a different segment of the region upstream of the mVSG 1 gene. Both of the transcripts, Xgt 11 2.2.4 and Agt 11 5.6.9, have been obtained as clones from Agt 11 cDNA library of IL30~O'metacyclic forms. Only Agt 11 2.2.4, cloned into plasmid pUC 118 and redesignated pcN 2.2.4 has been analysed in this thesis. Transcription of mRNA containing sequences in pcN 2.2.4 is developmentally regulated, being active only in the metacyclic forms of the parasite. Sequence analysis of pcN 2.2.4 transcript indicated that it has no open reading frame .cORF) and therefore dees not encode any protein. Unlike sequences which encode a majority of the different T. congolense VSGs analysed to date, the mVSG 1 gene and its upstream flanking sequences, i.e. its expression site (ES), are conserved in at least one other antigenic repertoire, ILNaR 3. This is the first evidence we are aware of, indicating the possible existence of isotypic antigen types (iso-VATs) among trypanosomes within the Nannomonas subgenus